KREATIVITAS HANDMADE - Hwihanus. Ak.,MM. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Creativity and entrepreneurship is a key to the success of one or more groups to competein the business world and beyond. Therefore, to achieve the success of an entrepreneur anda person who is not yet an entrepreneur requires a soul and knowledge aboutentrepreneurship and creativity in it, because the progress of time so fast someone will beleft if not have the skills, patience, and creativity. The process of quality entrepreneurship is not only seen from how much profit is earned,income earned, welfare is given. But there is one thing that is often forgotten by the publicto become a qualified entrepreneur that is creativity, with the existence of it in the soul ofone's entrepreneur then the business that is lived will be able to follow the development ofthe era, can compete in the tight competition, as well as no less important profit Gained willlast for a long time not just a moment when it's just buming Participants understand the tips on how to become an entrepreneur, the points that mustbe done to compete in the local, regional, and even global scale. They can also make anexample of a hanger product krudung derived from unused materials that previously thoughtout or have been unthinkable but have not been able to make it, finally the participants cansolve something that initially considered difficult.